DEVELOPING ASSESSMENT INSTRUMENTS FOR LEARNING OUTCOMES - Magdalena, Ina; Arwindi, Suci; Hasan, Saka Nayla (Transpublika Publisher, 2023)
This paper aims to provide understanding of assessment instruments for learning outcomes, focusing on benchmark learning outcome tools, norm-referenced and benchmark-referenced tests, validity, reliability, and practicality considerations, various types of tests, and the process of preparing assessment tools. Additionally, it explores performance-based assessment tools, emphasizing the significance of authentic assessment in an educational context. The research adopts a qualitative descriptive paradigm, oriented towards understanding nuances, perspectives, and subjective experiences related to learning outcomes assessment tools. This approach allows exploration of perceptions from teachers, students, and other stakeholders. Assessment is a crucial process in education, involving the collection of data to make informed decisions. This paper underscores the importance of various assessment types and techniques, ranging from daily quizzes to school exams. To ensure accurate and meaningful data, educators must use diverse assessment methods aligned with students' learning processes. The development of assessment tools is guided by determining types, forms, and variations based on specific needs. Effective assessment adheres to established principles, ensuring accuracy and reliability. The paper acknowledges potential shortcomings and errors, recommending the creation of a framework, use of relevant sources, effective collaboration, and time management when undertaking similar writing tasks.